Organizational communication a critical approach - Mumby, Dennis K. (SAGE Publications, Inc., 2013)
This first-of-its-kind textbook familiarizes students with the field of organizational communication--historically, conceptually, and practically--by examining where the field has been, as well as challenging students to reconsider their thoughts and beliefs to prepare for success in today's organizational settings. Revealing how management theory and research have been the key to understanding how corporations seek out methods of constructing our identities in ways that are consistent with corporate goals and values, Organizational Communication: A Critical Approach skillfully links theory and practice to provide relevance for student's daily lives. Key features: A thematic critical perspective on organizational communication provides a fresh lens to examine traditional theory and research, focusing on connections between communication, power, and control; Critical Case studies in each chapter provide practical applications of theoretical perspectives, showing students how theories can be critically applied to everyday organizational life; "Critical Technologies" boxes in each chapter give students a critical lens for observing how communication technologies impact organizational life; A chapter on branding and consumption (12) extends analysis of organizational communication beyond the workplace to examine the societal impact of organization on consumption and identity issues; A chapter on gender and feminism (9) and a chapter on difference (10) provide comprehensive accounts of gender and differences that illustrate how they are constructed through communication processes.